EFEKTIVITAS MODEL PEMBELAJARAN KOOPERATIF TIPE SNOWBALL THROWING TERHADAP HASIL BELAJAR MATEMATIKA SISWA - Karlina Karlina; Fitrah Amelia (CAHAYA PENDIDIKAN, 2019)
This research aims to determine the Effectiveness of the Cooperative Learning Model Snowball Throwing Type on students' mathematics learning outcomes. This type of research is a research experiment with research design One-Group Pretest-Posttest Design. The population of this study was XI SMKIT DBS 01 Batam Academic Year 2018/2019. The sampling technique is done by saturating sampling techniques with many students 19 students. The type of test given is a descriptive test consisting of 8 pretest questions and 8 posttest questions which then analyze the instrument using construct validity and reliability so that 8 valid and reliable questions are obtained with reliable values of pretest "0.684" and posttest "0.724" to be a matter of pretest and posttest. Normality test using Kolmogorov Smirnov with the results of normal pretest and posttest data. Hypothesis testing is done using the t test two correlated samples obtained sig. (0.00) ≤ . The results of this study indicate that the cooperative learning model of the snowball throwing type is effective against students' mathematics learning outcomes